A COMPARATIVE STUDY ON ORAL MUCOSAL LESIONS IN PATIENTS WITH DIABETES MELLITUS TYPE 2 AND HEALTHY SUBJECTS - AMBRISH MISHRA; ANSHUMAN SHARMA; MEDHA SINGH TIWARI; DIVASHREE SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The study was carried out to assess the prevalence of oral lesions in Type 2 Diabetes Mellitus (DM)patients and a control group comprising of non diabetic healthy patients. The findings of both groups were compared. Methods: A total of 110 patients with Type-2 diabetes mellitus (Group A) and 110 healthy patients (Group B) were enrolled in this study. Oral examination was done to assess and compare the prevalence of oral mucosal lesions in both groups. All variables were described as relative and absolute values. Frequency distribution tables were made, mean and standard deviations were calculated. Categorical variables were measured as percentages, while continuous variables were expressed as mean±standard deviation. Results: The male-to-female ratio of patients was 1:1.68 in Group A and 1:1.75 in Group B. The mean age was 52.68±11.42 years in Group A and 52.19±12.16 years in Group B. Majority of the patients (40.91%) reported a disease duration of 10–15 years. Oral lesions were more prevalent in the diabetic group 79.09% (n=87) than in the non-diabetic group (53.64%). The most common oral lesion was the coated tongue in the diabetic (71.81%) and the control group (40.91%). Conclusion: The prevalence of oral mucosal lesions was found to be higher in the diabetic group in comparison to the control group.